Evaluation of Castor Bark Powder as a Corrosion Inhibitor for Carbon Steel in Acidic Media - Santos,André de Mendonça (2017)
The inhibition effect of castor bark powder obtained from Ricinus communis on AISI 1020 carbon steel in acidic media (HCl 0.5 mol.L-1) has been studied by electrochemical impedance spectroscopy (EIS), polarization curves, scanning vibrating electrode technique (SVET) and weight loss measurements. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were employed as characterization techniques. The EIS and gravimetric results showed that the inhibitory efficiency increases with inhibitor concentration achieving 83%. Polarization curves indicated that the castor bark powder acts as mixed inhibitor. The adsorption of the powder components on the metal surface follows the Langmuir isotherm. The FTIR analyses indicate the presence of C, N and O heteroatoms, incorporated in functional groups mainly related to the presence of carboxylic acids as ricinoleic acid, which could be responsible for the inhibitory properties of the powder. SEM analyses showed that the corrosion process was retarded in the presence of inhibitor in the electrolyte, which was confirmed by SVET measurements. Therefore, the results indicate that castor bark powder has potential to be a corrosion inhibitor for carbon steel in acidic media.